“Why I founded Our Voice”: a Memoir - Hartoyo, NFN (Jurnal Perempuan, 2015)
Reformation Era has brought equality to any social movement such as LGBT circle. This era asked and gave opportunity to engage actively in the governance in many ways. Those that entered formal politics, or outside of formal politics such as NGO and community service. LGBT issue is becoming new term in the activism in Indonesia and that is why I established Suara Kita (Our Voice) to celebrate our identity and social justice. This paper narrated the establishment of this organization up to the present time under repression of the society.